KAJIAN KARAKTERISTIK FUNGSIONAL PRODUK ETANOLISIS CAMPURAN CPO (CRUDE PALM OIL) DAN PKO (PALM KERNEL OIL) PADA REAKSI ETANOLISIS TINGKAT DUA - Fizzaria Khasbullah; Murhadi Murhadi; Suharyono A.S. Suharyono A.S. (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
The objectives of this study were to determine the concentration of NaOH and ethanol containing NaOH to the weight of the media on level two ethanolysis reaction CPO-PKO mixture that produces the highest of antimicrobial activity, emulsifying properties and to investigate the distribution patterns of glyceride compounds. The treatments were ratio of ethanol containing NaOH to the weight of the media of level two ethanolysis reaction of CPO-PKO mixture, which were 1,20; 1,60 and 2,00 (v/w) and NaOH concentration to the weight of the media of ethanolysis reaction CPO-PKO mixture level two is 0,75; 1,0 and 1,25% (w/w). The results showed that the highest treatment was on treatment with ethanol at a ratio of 1,20 with NaOH concentration of 0,75%. The antimicrobial activities of Bacillus cereus, Salmonella typhimurium and natural microbial culture were 12,36%, 16,76 mm, 20,75 mm ​, 12,98 mm, and the highest emulsion stability power was found on 6% and 16,04% concentration. The level two ethanolysis product of CPO-PKO mixture showed a uniform distribution pattern on the the TLC plates in a row from the nearest to the farthest was the MG, DG, ALB and TG with Rf value of 0,03; 0,15; 0,43 and 0,74. Keywords: CPO (Crude Palm Oil), ethanolysis, PKO (Palm Kernel Oil)